13.3k views
0 votes
3(b − 6) = 9

b =
The test is timed

User Mgilson
by
5.3k points

2 Answers

4 votes

Answer:

b = 9

Explanation:


3(b - 6) = 9


3(b - 6) / 3 = 9 / 3


b - 6 = 9 / 3


b - 6 = 3


b - 6 + 6 = 3 + 6


b = 3 + 6


b = 9

User Tiago Mendes
by
5.2k points
0 votes

Answer:

b = 9

Explanation:

3(b − 6) = 9

3b - 18 = 9

3b = 9 + 18

3b = 27

b = 9

User Humanoid
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.